Thermo-Responsive Hydrogels Encapsulating Targeted Core-Shell Nanoparticles as Injectable Drug Delivery Systems - Elif Gulin Ertugral-Samgar; Ali Murad Ozmen; Ozgul Gok (MDPI AG, 2023)
As therapeutic agents that allow for minimally invasive administration, injectable biomaterials stand out as effective tools with tunable properties. Furthermore, hydrogels with responsive features present potential platforms for delivering therapeutics to desired sites in the body. Herein, temperature-responsive hydrogel scaffolds with embedded targeted nanoparticles were utilized to achieve controlled drug delivery via local drug administration. Poly(N-isopropylacrylamide) (pNIPAM) hydrogels, prepared with an ethylene-glycol-based cross-linker, demonstrated thermo-sensitive gelation ability upon injection into environments at body temperature. This hydrogel network was engineered to provide a slow and controlled drug release profile by being incorporated with curcumin-loaded nanoparticles bearing high encapsulation efficiency. A core (alginate)-shell (chitosan) nanoparticle design was preferred to ensure the stability of the drug molecules encapsulated in the core and to provide slower drug release. Nanoparticle-embedded hydrogels were shown to release curcumin at least four times slower compared to the free nanoparticle itself and to possess high water uptake capacity and more mechanically stable viscoelastic behavior. Moreover, this therapy has the potential to specifically address tumor tissues over-expressing folate receptors like ovaries, as the nanoparticles target the receptors by folic acid conjugation to the periphery. Together with its temperature-driven injectability, it can be concluded that this hydrogel scaffold with drug-loaded and embedded folate-targeting nanoparticles would provide effective therapy for tumor tissues accessible via minimally invasive routes and be beneficial for post-operative drug administration after tumor resection.